Transmission characteristics of circular–linear edge dislocation vortex beams in optical nonlocal medium - Zhi-Ping Dai; Jia-Qi Liu; Peng Pan; Zhao-Guang Pang; Zhen-Jun Yang (Results in Physics, 2024)
The transmission characteristics of circular–linear edge dislocation vortex (CLEDV) beams in optical nonlocal medium is investigated analytically and numerically in detail. The analytical expression for the transmission of CLEDV beams is derived, and the transmission characteristics of CLEDV beams are illustrated in figures. The influence of various parameters of CLEDV beams on transmission characteristics is discussed, including statistical spot size, input power, topological charge, etc. The results indicate that the main transverse intensity of CLEDV beams can maintain a crescent shaped distribution and rotate periodically under the influence of topological charges. For different input powers, the variations of the statistical spot size of CLEDV beams in two transverse directions exhibit diverse behaviors: they can be diametrically opposite, simultaneously expand or compress, remain constant in one direction while periodically changing in the other. This complexity highlights the intricate dynamics of CLEDV beams in optical nonlocal medium.